Grazing can reduce wildfire risk amid climate change - Pillar, Valério D.; Overbeck, Gerhard E. (Science (American Association for the Advancement of Science), 2025)
Over half of Earth’s land surface is covered with fire-prone vegetation , with grassy ecosystems—such as grasslands, savannas, woodlands, and shrublands—being the most extensive . In the context of the climate crisis, scientists worldwide are exploring adaptation measures to address the heightened fire risk driven by more frequent extreme climatic conditions such as droughts and heatwaves, as well as by non-native plant invasions that increased fuel loads and altered fire regimes. Although fire is intrinsic to grassy ecosystems , rising exposure to wildfire smoke harms human health and the environment. Here, we argue that grazing management in grassy ecosystems could help reduce wildfire risk and its consequences.